Lengthened partial repetitions elicit similar muscular adaptations as full range of motion repetitions during resistance training in trained individuals - Wolf, Milo; Androulakis Korakakis, Patroklos; Piñero, Alec; Mohan, Adam E.; Hermann, Tom; Augustin, Francesca; Sapuppo, Max; Lin, Brian; Coleman, Max; Burke, Ryan; Nippard, Jeff; Swinton, Paul A.; et al. (PeerJ, 2025)
Purpose Resistance training using different ranges of motion may produce varying effects on musclular adaptations. The purpose of this study was to compare the effects of lengthened partial repetitions (LPs) vs. full range of motion (ROM) resistance training (RT) on muscular adaptations. Methods In this within-participant study, thirty healthy, resistance-trained participants had their upper extremities randomly assigned to either a lengthened partial or full ROM condition; all other training variables were equivalent between limbs. The RT intervention was an 8-week program targeting upper-body musculature. Training consisted of two training sessions per week, with four exercises per session and four sets per exercise. Muscle hypertrophy of the elbow flexors and elbow extensors was evaluated using B-mode ultrasonography at 45% and 55% of humeral length. Muscle strength-endurance was assessed using a 10-repetition-maximum test on the lat pulldown exercise, both with a partial and full ROM. Data analysis employed a Bayesian framework with inferences made from posterior distributions and the strength of evidence for the existence of a difference through Bayes factors. Results Both muscle thickness and unilateral lat pulldown 10-repetition-maximum improvements were similar between the two conditions. Results were consistent across outcomes with point estimates close to zero, and Bayes factors (0.16 to 0.3) generally providing “moderate” support for the null hypothesis of equal improvement across interventions. Conclusions Trainees seeking to maximize muscle size should likely emphasize the stretched position, either by using a full ROM or LPs during upper-body resistance training. For muscle strength-endurance, our findings suggest that LPs and full ROM elicit similar adaptations.
Keywords: Full rom; Lengthened partials; Hypertrophy; Range of motion; Long muscle lengths; Long length partials; Full range of motion; Muscle growth; Strength